Analisis Kejahatan dan Hukuman tehadap Tantangan Deterministik Kausal secara Sosial yang Menyebabkan Pertanggungjawaban Pidana - Hisam Ahyani; Muhamad Ghofir Makturidi; Farhatun Sa’diyah; Dien Kalpika Kasih; Haris Maiza Putra (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2022)
Crime and punishment are 1) a behavior, 2) a type of social phenomenon in the interactions that are built between humans, 3) natural and social phenomena, 4) including interactions between people in social life, 5) are considered as deterministic mechanical processes based on the law of causality. So that nowadays the study of crime and punishment needs to be developed in order to realize national development. This research method is a normative research where causal deterministic aims at sentencing and is not only based on the concept of retributive justice, but also on the principle of benefit generated in the sense that it aims to prevent the recurrence of similar crimes and thereby create order and national security. The results of the study show that crime and punishment against socially causal deterministic challenges that lead to criminal liability is a necessity as Satjipto Rahardjo revealed that law always evolves following human development and follows the needs and values that live in humans to realize social justice for all citizens. Indonesia.